Effects of drying methods on non-volatile taste components of Stropharia rugoso-annulata mushrooms. (June 2020) - Hu, Si; Feng, Xi; Huang, Wen; Ibrahim, Salam A.; Liu, Ying
Abstract: In this study, the pileus and stipe of Stropharia rugoso-annulata were separately dehydrated using natural air drying (NAD), hot air drying (HAD) and vacuum freeze drying (VFD), the proximate composition and non-volatile compounds (soluble sugars, organic acids, free amino acids and 5′-nucleotides) were investigated. We found that the contents of free amino acids (37.21–51.07 mg/g) and 5′-nucleotides (18.33–22.76 mg/g) in pileus were higher than those of stipe. The contents of MSG-like amino acids (3.61–11.70 mg/g) and flavor 5′-nucleotides (5.47–5.94 mg/g) in pileus were also higher than those of stipe. The dried S. rugoso-annulata treated with VFD had the highest levels of soluble sugars, organic acids, free amino acids and 5′-nucleotides. We found that NAD and HAD had medium levels of MSG-like amino acids (7.95–11.7 mg/g) and VFD had low levels of MSG-like amino acids (3.16–3.61 mg/g). Moreover, HAD had the highest level of equivalent umami concentration (EUC) value (784.05 g MSG/100 g). Our results suggested that VFD was better to preserve the non-volatile compounds in S. rugoso-annulata, but HAD would be a potential method to produce umami concentration of dried S. rugoso-annulata . Highlights: Natural air drying (NAD), hot air drying (HAD), vacuum freeze drying (VFD) were studied. The taste components in pileus and stipe of S. rugoso-annulata were examined. The taste components levels in pileus were higher than those of stipe. Mushrooms treated with VFD had the highest level of taste components. HAD had the highest level of equivalent umami concentration (EUC) value.